Os Plattenbau e o projeto socialista em Berlim. Proposta de intervenção no bloco residencial - Mafalda Marques Neves (2020)
PLATTENBAU | INDUSTRIALISATION | HOUSING | REHABILITATION On the east side of Berlin, shaped by the heritage of GDR, are the testimonies of a city of a socialist genesis, characterized by the residential districts and the Plattenbau blocks, built during the post-war period. The problematization of this architecture on the contemporary horizon regarding the preservation and updating of Plattenbau buildings. Thereby, this research focuses on one of the city's neighbourhoods, Neu-Hohenschönhausen, where a number of problems - architectural and social - are identified, which are transversal to the former GDR's buildings. It also provides a concrete case study, from which an architectural project has been developed, which seeks to overcome the constraints that hinder the regeneration and integration of the socialist building in a current reality.